1992
DOI: 10.1161/01.cir.85.3.1152
|View full text |Cite
|
Sign up to set email alerts
|

Improved regional myocardial blood flow, left ventricular unloading, and infarct salvage using an axial-flow, transvalvular left ventricular assist device. A comparison with intra-aortic balloon counterpulsation and reperfusion alone in a canine infarction model.

Abstract: Background. It has been suggested that left ventricular unloading at the time of reperfusion provides superior infarct salvage over reperfusion alone. The purpose of this study was to show that the Hemopump transvalvular axial-flow left ventricular assist device provides superior left ventricular unloading, ischemic zone collateral blood flow, and infarct size reduction compared with intra-aortic balloon counterpulsation and reperfusion alone.Methods and Results. Eighteen dogs were instrumented with regional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(49 citation statements)
references
References 22 publications
3
45
0
1
Order By: Relevance
“…Ventricular unloading may reduce myocardial infarct size through enhanced hemodynamics, preserved energetics, and activation of cardioprotective mechanisms [48,116]. Despite limited unloading potency, some animal infarct model studies found improved myocyte recovery with IABP use [117,118]. However, as described above, the CRISP-AMI study [101] found no difference in mean final infarct size between STEMI patients (not complicated by cardiogenic shock) who received routine IABP compared with those who did not.…”
Section: Future Directions: Myocyte Protection and Recoverymentioning
confidence: 98%
“…Ventricular unloading may reduce myocardial infarct size through enhanced hemodynamics, preserved energetics, and activation of cardioprotective mechanisms [48,116]. Despite limited unloading potency, some animal infarct model studies found improved myocyte recovery with IABP use [117,118]. However, as described above, the CRISP-AMI study [101] found no difference in mean final infarct size between STEMI patients (not complicated by cardiogenic shock) who received routine IABP compared with those who did not.…”
Section: Future Directions: Myocyte Protection and Recoverymentioning
confidence: 98%
“…Thus, many researchers have discussed the effect of LVADs on myocardial perfusion, but it remains incompletely understood. [43][44][45][46][47] A counter-pulse effect may be useful for increasing coronary perfusion with increasing aortic pressure in the diastolic phase. 44, [48][49][50] Therefore, in the present study we focused on CoF, which we expected to control with the cf-LVAD using the pulsatile driving technique.…”
Section: Umeki a Et Almentioning
confidence: 99%
“…19 However, recent studies that have measured coronary flow velocity directly using a Doppler catheter, 2 Doppler guide wire, 3 transesophageal echocardiography 20 or transthoracic echocardiography 6 also reported different effects of IABP on coronary flow, namely that it increased 2,6 or remained unchanged. 3,7 Some investigators 3,5 have suggested that the inconsistency in the coronary flow velocity response during IABP may be related to differences in the severity of the coronary artery stenoses. Kern et al 4 found that IABP augmentation increased the proximal coronary flow velocity, as measured by a Doppler catheter, 4 and they also reported that coronary flow velocity was unaffected by IABP augmentation in the presence of severe coronary artery stenosis.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Although the former effect is well recognized, the latter effect remains controversial, 2-6 because previous studies have reported that coronary blood flow during IABP either increased 2,6 or remained unchanged. 3,7 Percutaneous coronary intervention (PCI) is used as a treatment for acute myocardial infarction (AMI), and one of its major complications is the angiographic no-reflow phenomenon. Once this phenomenon occurs, the prognosis is extremely poor.…”
mentioning
confidence: 99%